Modelling and evaluation of brittle shear effects on the seismic performance and loss assessment of RC buildings. (15th January 2023) - Peres, R.; Couto, R.; Sousa, I.; Castro, J.M.; Bento, R.
Highlights: The seismic vulnerability of old RC buildings with extremely low transversal reinforcement ratios in columns is examined. The inadequacy of the available analytical shear models in literature, as the lack of numerical modelling approaches, to simulate the shear failure that is expected to occur in this type of columns, i.e., prior to flexural yielding of the element, is highlighted. Proposal of a simple numerical modelling approach, in Opensees, to incorporate this type of shear brittle failure. Abstract: This paper focuses on the seismic vulnerability assessment of old RC buildings prone to brittle shear effects, i.e., with extremely low transversal reinforcement ratios in columns. Within this context, two limitations are identified: 1) the inadequacy of the available analytical shear models in literature since most of them are based on experimental results performed on specimens with transversal reinforcement ratios higher than those found in old buildings and 2) the lack of simplified numerical modelling approaches to simulate shear failure prior to flexural yielding of the element's longitudinal reinforcement. To overcome these limitations, a simple modelling approach is proposed, and its impact is evaluated through seismic and loss assessment of a RC structure typical of the Lisbon building stock. For comparison purposes, the building is modelled using two different numerical models: one that only captures the nonlinear flexural behaviour of the structural elements, and another that considers both flexural non-linear behaviour and brittle shear failure through the incorporation of uncoupled shear springs that limit the maximum strength that the RC columns can withstand. The seismic performance evaluation is carried out through nonlinear static and Incremental Dynamic Analysis (IDA). Collapse assessment is evaluated considering two different collapse criteria, namely global failure (GF) based on the identification of flattening of the IDA curves and first component failure (FCF) which is conducted based on post-processing analysis of shear forces and inter-storey drifts. The results show that the proposed modelling approach combined with the GF collapse criterion leads to estimates of expected annual losses (EAL) compatible with those reported in other studies found in the literature. Additionally, it is observed that the adoption of a first component failure criterion based on shear force control conducts to consistent estimates of EAL.